2021
DOI: 10.1038/s41467-021-23786-6
|View full text |Cite
|
Sign up to set email alerts
|

Heteromeric HSFA2/HSFA3 complexes drive transcriptional memory after heat stress in Arabidopsis

Abstract: Adaptive plasticity in stress responses is a key element of plant survival strategies. For instance, moderate heat stress (HS) primes a plant to acquire thermotolerance, which allows subsequent survival of more severe HS conditions. Acquired thermotolerance is actively maintained over several days (HS memory) and involves the sustained induction of memory-related genes. Here we show that FORGETTER3/ HEAT SHOCK TRANSCRIPTION FACTOR A3 (FGT3/HSFA3) is specifically required for physiological HS memory and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 61 publications
6
130
1
2
Order By: Relevance
“…Interestingly, chromatin immunoprecipitation analysis demonstrated a significant depletion in global deposition of H3K9me2 and H3K4me3 repressing marks in Arabidopsis plants subjected to prolonged heat stress treatments [40]. As mentioned in the introduction, an important HSF factor, HSFA2, forms heterodimers with HSFA3 and interacts with additional HSFs to recruit H3K4 histone methyltransferases and mediate histone H3K4 hypermethylation to maintain transcriptional memory during HS recovery [44,45] (Figure 2). In recent years, a lot of effort has been made to elucidate the role of histone acetylation in mediating heat stress-induced responses.…”
Section: Histone Modificationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, chromatin immunoprecipitation analysis demonstrated a significant depletion in global deposition of H3K9me2 and H3K4me3 repressing marks in Arabidopsis plants subjected to prolonged heat stress treatments [40]. As mentioned in the introduction, an important HSF factor, HSFA2, forms heterodimers with HSFA3 and interacts with additional HSFs to recruit H3K4 histone methyltransferases and mediate histone H3K4 hypermethylation to maintain transcriptional memory during HS recovery [44,45] (Figure 2). In recent years, a lot of effort has been made to elucidate the role of histone acetylation in mediating heat stress-induced responses.…”
Section: Histone Modificationsmentioning
confidence: 87%
“…Plant adaptation to heat stress also relies on a number of epigenetic mechanisms, including chromatin remodeling, chromatin-associated SUMOylation [26], histone modifications [40,[44][45][46][47][48][49][50] and ncRNA regulation [60]. Although a lot of effort has been put on elucidating the epigenetic adaptation to heat acclimation, the current literature is still lacking evidence on how different factors such as transcription factors, ncRNAs and chromatin modifications cooperate to configure heat stress responses.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…5b), suggesting a recent event of transcriptional activation (Ng et al ., 2004; D’Urso et al ., 2016). Moreover, H3K4 hypermethylation contributes to the priming of gene expression in HS and to pathogen defence responses (Jaskiewicz et al ., 2011; Mozgova et al ., 2015; Friedrich et al ., 2021). Strikingly, H3K4 methylation has a role in cold signalling and vernalisation as well (reviewed in Luo & He, 2020; Pandey et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research from the last few years indicated that HS memory is partly based on epigenetic mechanisms. In Arabidopsis, at the whole plant level, HS memory lasts for up to 5 d and results in increased survival after a HS that is lethal to a naïve (nonprimed) plant (Charng et al ., 2006; Stief et al ., 2014; Friedrich et al ., 2021). At the level of gene expression, this is reflected by two types of transcriptional memory (Fig.…”
Section: Epigenetic Regulation Of Hs Memorymentioning
confidence: 99%
“…Strong/rapid expression of sHSP genes including HSP21 , HSP22 , and HSP17.6C is observed in primed plants compared to non-primed plants ( Yamaguchi et al, 2021 ). FORGETTER3 ( FGT3 )/ HSFA3 is needed to retain HS memory for several days following HS exposure ( Friedrich et al, 2021 ). A recent discovery showed that genes encoding stem cell regulators such as CLAVATA1 ( CLV1 ), CLV3 , and HSP17.6A , and the primary carbohydrate metabolism gene FRUCTOSE-BISPHOSPHATE ALDOLASE 6 ( FBA6 ) are involved in the HS transcriptional memory in the shoot apical meristem ( Olas et al, 2021 ).…”
Section: Transcriptional Regulation Of Heat Shock Proteins In Plants ...mentioning
confidence: 99%